Closing the Gender Pay Gap and Individual Task Profiles: Women s Advantages from Technological Progress - Alexandra Fedorets (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In the present paper I provide novel evidence on the formation of the gender pay gap with respect to directly measured job task contents. Using high-quality administrative employment data for Germany, and augmenting these by individual-level task information, I provide detailed evidence on the evolution of task contents and their gender-specific remuneration across and within occupations for both genders. The main finding of the paper is that the formation of the pay gap is substantially driven by the relative prices for non-routine cognitive tasks. Moreover, I document convergence in prices for non-routine cognitive tasks and convergence of tasks contents within occupational groups. The only exception from this general finding constitutes the top of the wage distribution, where the substantial difference in prices for non-routine cognitive tasks is persistent and the pay gap is not narrowing.
Keywords: J24; J31; J16; 330